The Graphic privacy in vector graphics design for children's publications (Al-Academy, 2022)
The graphic privacy feature is one of the most important specifications for the existence of any type of design achievements alike, which is one of the graphic products with its multiple data, and from here the current research investigates the graphic privacy of vector graphics design with all its technical descriptions and concepts associated with it and the possibility of achieving it to the best that it should be from Where its formal structure in children's publications, where the structural structure of the current research came from the first chapter, which contained the research problem, which came according to the following question: What is the graphic privacy in the design of vector graphics in children's publications? It also determined the importance of research in the theoretical and applied aspects. The goal of the research was determined to reveal graphic privacy in the design of vector graphics. It also identified three limits for research regarding the subject, time and place, as well as defining the terms of privacy and graphic privacy and vector graphics. The second chapter also included the theoretical framework related to the knowledge of the subject of the research, and the theoretical framework included analysis and criticism of models of children's publications, then the research came out with results from them. The dominant unit appeared in computer vector graphics through vector graphic processors, and thus excitement and strangeness were achieved. The research also came out with recommendations for the current study. Then the research was included in the list of Arab and foreign sources related to the research